Absorption heat transformer - state-of-the-art of industrial applications. (May 2021) - Cudok, Falk; Giannetti, Niccolò; Ciganda, José L. Corrales; Aoyama, Jun; Babu, P.; Coronas, Alberto; Fujii, Tatsuo; Inoue, Naoyuki; Saito, Kiyoshi; Yamaguchi, Seiichi; Ziegler, Felix
Abstract: The use of waste heat or low-exergy heat sources represents a strategic opportunity to reduce the environmental footprint and operation cost of industrial processes. The absorption heat transformer, also known as absorption heat pump type II, is a thermal machine which can boost the temperature of a heat flow by using a negligible amount of electrical power. However, owing to the lack of established technical knowledge and the absence of comprehensive recordings of successful heat transformer applications, the feasibility and reliability of absorption heat transformers have been questioned and the diffusion of this technology remained limited. Therefore, in this paper, all the industrial applications of the absorption heat transformer that are recorded in previous literature and yet unpublished reports are presented and discussed. In addition to literature research, intense knowledge exchange with three leading manufacturers of absorption heat transformers gave an accurate perspective on the technological level of commercial products and operative installations. It is shown that between 1981 and 2019, 48 absorption heat transformers have been installed in 42 plants with a total capacity of ≈ 134 MW . Two main implementation periods, separated by 25 years of infrequent heat transformer installations, have been recognised. More than 74% of the installations were in Asia. Approximately 61 % of the heat transformer installations were applied into the chemical industry. Therefore, through the analysis of the technical challenges and their solutions, along with related economical aspects of heat transformer installations, the effective state-of-the-art of this technology is presented and discussed. Highlights: Overview of commercial absorption heat transformers. Industrial heat recovery. Application of heat transformers in industrial processes.